LCIs and PWM-VSIs for the Petroleum Industry: A Torque Oriented Evaluation for Torsional Analysis Purposes - Mon-Nzongo, Daniel Legrand; Ekemb, Gabriel; Song-Manguelle, Joseph; Ipoum-Ngome, Paul Gistain; Jin, Tao; Doumbia, Mamadou L. (IEEE transactions on power electronics, 2019)
This paper proposes an analytical time and frequency domains evaluation of torque harmonics produced by high-power load-commutated-inverters (LCIs) and pulsewidth-modulated (PWM) voltage-source inverters for adjustable speed applications. These drive systems are used in petrochemical and mining industries, where driven loads have multi-inertia or long shafts that are potentially subject to torsional mode excitation. Such excitation may lead to accelerated fatigue, system failure, and loss of production, and in turbine-generator sets, to system blackout. The investigated power conversion topologies are multi-pulse LCIs (6/6 and 12/12-pulse systems), parallel connected three-level neutral-clamped-converters with non-interleaved and interleaved PWM signals, as well as series-connected H-bridge multi-level inverters, single thread and four threads supplying a 12-phase machine and parallel connection of four threads converter systems with interleaved PWM commands. They are the most used variable frequency drives in the megawatt range, both with synchronous and induction machines, in the petrochemical industry. The time and frequency domains of the machine's air-gap torque is calculated from the motor's voltage and stator's current waveforms, this proven method is independent from the type of ac machine. More than 50 simulated operating points are discussed and experimental results for NPC and cascaded inverters are also presented.